STUDI KASUS PADA IBU HAMIL TRIMESTER III DENGAN KEHAMILAN POSTDATE DI PMB “S” JETIS PONOROGO - Indah Dian Nirwana; Hayun Manudyaning Susilo; Ririn Ratnasari (Universitas Muhammadiyah Ponorogo, 2022)
pPostdate pregnancy is one of the great danger pregnancies, this can cause more serious risk and confusions for both the mother and the embryo during pregnancy, labor or post pregnancy. Postdate pregnancy is a pregnancy that surpasses the assessed day of birth (HPL) with a gestational time of 40-42 weeks. The motivation behind this investigation was to give coherence of care to Mrs. W G2P10001 in PMB